Risk assessment of listeria monocytogenes in ready- to- eat foods: Technical report (FAO, 2004)
Cases of listeriosis in food appear to be predominantly associated with ready-to-eat products. This publication sets out the full technical report of the risk assessment, jointly undertaken by the Food and Agriculture Organization and the World Health Organization, into the problems posed by the pathogen in ready-to-eat foods. It includes data and methodology relevant to the four steps of risk assessment (hazard identification, exposure assessment, hazard and risk characterisation) and also contains four example assessments addressing the risk of listeriosis associated with fresh milk, ice cream, fermented meats and cold-smoked fish, products selected to represent typical classes of ready-to-eat products. A summary of the technical report is available separately (ISBN 9251051267).